Coping Strategies of Women Following the Diagnosis of Infertility in Their Spouses: A Qualitative Study - Ali Taghipour; Fatemeh Zahra Karimi; Robab Latifnejad Roudsari; Seyed Reza Mazlom (Journal of Evidence-Based Care, 2020)
Background: Infertility affects women more profoundly than men, even when the male partner is the cause of infertility. Therefore, identifying the coping strategies of women in confrontation with their husbands' infertility is very important. Aim: This study aimed to explore women’s coping strategies following the diagnosis of infertility in their husbands. Method: This qualitative study was performed on 18 women whose husbands were diagnosed with infertility. The subjects were selected from those who referred to Milad Fertility Clinic and public health centers in Mashhad, Iran, through purposive sampling within 2014-2016. The data were collected by conducting semi-structured interviews. Data analysis was manually carried out using conventional content analysis. Results: The main theme emerged from the content analysis was the attempts to overcome the threat, including two categories, namely emotional coping and active coping. Emotional coping included strategies like attributing infertility to herself and others, selective disclosure, religious coping, seeking emotional support, as well as being considerate and offering verbal support to the spouse. active coping consisted of strategies namely attempting to verify the diagnosis, accepting infertility, searching for information, adhering to medical and surgical treatments, trying fertility superstitions, using alternative medicine, and changing lifestyle. Implications for Practice: Women may use a diverse set of coping strategies to adapt to their husbands’ infertility. A deep perception of these strategies is critical for controlling and managing the consequences of this diagnosis, designing interventions to strengthen preferred actions and strategies, as well as facilitating women’s coping with the infertility crisis of their spouses.